Choosing to Choose: The Effects of Decoys and Prior Choice on Deferral - Hedgcock, William M.; Rao, Raghunath Singh; Chen, Haipeng (Allan) (Management Science, 2016)
Sellers are often more interested in inducing buyers to make a choice—any choice—than in influencing which option they choose. For example, many retailers are more concerned about maximizing customer purchases within categories than influencing which brand is purchased in any particular category. Although this issue is important to researchers and practitioners, research on how contextual factors, such as decoys and prior decisions, affect whether consumers will “choose to choose” is scarce. We propose a reference-dependent model to fill this gap. This model unites several streams of research and leads to novel predictions that are tested and supported in four experiments. The paper concludes with a discussion of the theoretical and practical implications of the findings. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2289 . This paper was accepted by Pradeep Chintagunta, marketing.